2018
DOI: 10.1074/mcp.ra118.000961
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Mitochondrial Defects in a Nonalcoholic Fatty Liver Disease Mouse Model Are Associated with Increased Degradation of Oxidative Phosphorylation Subunits

Abstract: Nonalcoholic fatty liver disease (NAFLD) is associated with hepatic mitochondrial dysfunction characterized by reduced ATP synthesis. We applied the HO-metabolic labeling approach to test the hypothesis that the reduced stability of oxidative phosphorylation proteins contributes to mitochondrial dysfunction in a diet-induced mouse model of NAFLD. A high fat diet containing cholesterol (a so-called Western diet (WD)) led to hepatic oxidative stress, steatosis, inflammation and mild fibrosis, all markers of NAFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 55 publications
3
36
0
1
Order By: Relevance
“…The Krebs cycle has a central role in liver metabolism, connecting hepatic fatty acid and glucose-related pathways. Abnormal cellular [20] and circulating [21] Krebs cycle intermediates are closely associated with mitochondrial dysfunction as was demonstrated in numerous studies [22][23][24][25]. Given the decreased activity in respiratory chain complexes in NAFLD [4], perturbations in cellular concentrations of Krebs cycle intermediates are expected.…”
Section: Resultsmentioning
confidence: 99%
“…The Krebs cycle has a central role in liver metabolism, connecting hepatic fatty acid and glucose-related pathways. Abnormal cellular [20] and circulating [21] Krebs cycle intermediates are closely associated with mitochondrial dysfunction as was demonstrated in numerous studies [22][23][24][25]. Given the decreased activity in respiratory chain complexes in NAFLD [4], perturbations in cellular concentrations of Krebs cycle intermediates are expected.…”
Section: Resultsmentioning
confidence: 99%
“…The stressors leading to senescence include telomere shortening due to replicative exhaustion, DNA or chromatin structure and mitochondrial dysfunction [15][16][17][18][19]. Recent reports indicated that mitochondrial dysfunction plays an important role in initiating inflammatory responses and cellular senescence and has significance in the pathogenesis of lung disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria increase fatty acids (FAs) β-oxidation (mt-FAO) to restrain hepatic fat accumulation [ 12 ]. However, the abolished mt-FAO response in NAFLD can be associated with different mitochondrial alterations, such as reduced oxidative phosphorylation (OXPHOS), diminished ATP production and enhanced sensitivity for mitochondrial permeability transition pore (mPTP) opening [ 12 , 13 , 14 ]. The progression of NAFL towards NASH in a nonreversible manner was reported to involve a prooxidative state and mitochondrial-induced reactive oxygen species (ROS) production, which ultimately alter cellular signaling cascades leading to hepatocellular inflammation and fibrosis [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%